(untitled) - Fitzgerald, A. E.; A.E. Fitzgerald; Charles Kingsley; Jr.; Stephen D. Umans (Boston, Mass.)
The exciting new sixth edition of "Electric Machinery" has been extensively updated while retaining the emphasis on fundamental principles and physical understanding that has been the outstanding feature of this classic book. This book covers fundamental concepts in detail as well as advanced topics for readers who wish to cover the material in more depth. Several new chapters have been added, including a chapter on power electronics, as well as one on speed and torque control of dc and ac motors. This edition has also been expanded with additional examples and practice problems. The use of MATLAB has been introduced to the new edition, both in examples within the text as well as in the chapter problems
Keywords: Electric machinery